2022
DOI: 10.31599/jces.v3i2.1549
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Jigsaw Cooperative Learning Model on Learning Outcomes of Dribbling and Passing Using the Back of the Foot Football Game in Class VII Students of SMP

Abstract: This study aims to determine the effect of the jigsaw cooperative learning model on learning outcomes of dribbling and passing by using the instep of a soccer game in class VII students of SMP Negeri 1 Pekutatan. This type of research is quasi-experimental research. The population is all students in class VII A and VII B of SMP Negeri 1 Pekutatan for the 2021/2022 school year with a total of 66 students. The sample used random sampling. The research was conducted in twelve meetings. Learning outcome data is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The exploration and influence of teaching models are also mostly explored through empirical research, with the integration and exploration of different PE models such as physical education model, teaching games of understanding model, and teaching personal and social responsibility model all recognized through teaching experiments ( Kirk, 2013 ; Kipp and Bolter, 2020 ; Anggreni et al, 2022 ). In the blend of the teaching models for PE and CL, teachers found that after 24 sessions of continuous implementation, they fostered a conducive learning environment, leading to comprehensive student development across various domains ( Gil-Arias et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exploration and influence of teaching models are also mostly explored through empirical research, with the integration and exploration of different PE models such as physical education model, teaching games of understanding model, and teaching personal and social responsibility model all recognized through teaching experiments ( Kirk, 2013 ; Kipp and Bolter, 2020 ; Anggreni et al, 2022 ). In the blend of the teaching models for PE and CL, teachers found that after 24 sessions of continuous implementation, they fostered a conducive learning environment, leading to comprehensive student development across various domains ( Gil-Arias et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%